2021
DOI: 10.1002/acp.3817
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of temporal experience in active and passive waiting situations

Abstract: Activities can have substantial impacts on temporal experience. We investigated how the impact of being active develops dynamically over the course of long waiting times. Participants waited in a library building, either sitting passively or walking around actively, for between 60 and 100 minutes. Retrospectively, they reported how different aspects of their temporal experiences developed throughout their wait: duration judgments, passage of time judgments, and general awareness of time.Duration was estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…On the contrary, studies have shown that individuals prefer being engaged in alternative activities instead of persevering and waiting. The experience of engaged time is entirely different from the time spent passively waiting [64]. The lack of activity while waiting allows an individual to pay more attention to the passage of time and increase one's awareness of oneself [65].…”
Section: Physical Layermentioning
confidence: 99%
“…On the contrary, studies have shown that individuals prefer being engaged in alternative activities instead of persevering and waiting. The experience of engaged time is entirely different from the time spent passively waiting [64]. The lack of activity while waiting allows an individual to pay more attention to the passage of time and increase one's awareness of oneself [65].…”
Section: Physical Layermentioning
confidence: 99%